Adipocytokine and Ghrelin responses to acute exercise and sport training in children during growth and maturation - Jürimäe, J. (Pediatric Exercise Science, 2014)
Physical exercise is known to regulate energy balance. Important to this regulatory system is the existence of several peptides that communicate the status of body energy stores to the brain and are related to the body fatness including leptin, adiponectin and ghrelin. These hormones assist in regulating energy balance as well as somatic and pubertal growth in children. It appears that rather few studies have investigated the responses of leptin, adiponectin and ghrelin to acute exercise and these studies have demonstrated no changes in these peptides as a result of exercise. Leptin levels are decreased and may remain unchanged advancing from pre-puberty to pubertal maturation in young male and female athletes. A limited number of studies indicate that adiponectin levels are not different between prepubertal and pubertal athletes and untrained controls. However, in certain circumstances circulating adiponectin could be increased in young athletes after onset of puberty as a result of heavily increased energy expenditure. Ghrelin levels are elevated in young sportsmen. However, pubertal onset decreases ghrelin levels in boys and girls even in the presence of chronically elevated energy expenditure as seen in young athletes. Ghrelin may also be used as an indicator of energy imbalance across the menstrual cycle in adolescent athletes. There are no studies with high-molecular-weight adiponectin and only very few studies with acylated ghrelin responses to acute exercise and chronic training have been performed in young athletes. Since these forms of adiponectin and ghrelin have been thought to be bioactive forms, further studies with these specific forms of adiponectin and ghrelin are needed. In conclusion, further studies should be conducted to investigate the response of these hormones to acute and chronic negative energy balance to better understand their role in regulating energy balance during growth and maturation in young athletes.